Implementasi Kebijakan Ketahanan Pangan dalam Mendukung Sustainable Development Goals (SDGs) di Indonesia: Studi Literatur - Ayyi Afifah; Devi Novita Sari; Siti Nurlaila; Dilla Erlianti (Universitas 17 Agustus 1945 Semarang, Indonesia, 2026)
Food security is a complex issue closely related to various aspects such as agriculture, nutrition, health, and the environment. In the context of global development, food security is an integral part of the Sustainable Development Goals (SDGs), particularly Goal 2: Zero Hunger. This study aims to analyze the implementation of food security policies in supporting the achievement of the SDGs and to identify the factors that hinder the successful implementation of these policies. This research uses a qualitative approach with a literature study method, examining various secondary data sources including books, journal articles, laws and regulations, official government reports, mass media, and relevant online publications. The results show that the Indonesian government has undertaken various efforts to achieve food security through strengthening regulations, starting from Law Number 18 of 2012, Government Regulation Number 17 of 2015, and Presidential Regulation Number 125 of 2022. These efforts are supported by increased budget allocation, local wisdom-based food diversification programs, food estate programs, and strengthening national food reserves through cross-sectoral coordination. However, the implementation of these policies still faces four structural constraints, namely high population growth, the conversion of agricultural land, the impact of climate change on agricultural productivity, and low interest among the younger generation, which threatens farmer regeneration. The implications of this study indicate that the successful implementation of food security policies in supporting the achievement of the SDGs requires comprehensive, sustainable strategies and effective cross-sector collaboration.